PSYCHOLOGICAL FEATURES OF CREATIVITY IN PRESCHOOL CHILDREN - Abduqodirova D.E. (Modern American Journals, 2025)
This article examines the psychological characteristics of creativity in preschool-age children. Creativity is a higher form of human thinking directly linked to a child’s life experience, perception, imagination, emotional state, and motivational needs. The study analyzes psychological factors that influence the development of creative thinking in children, as well as the role of upbringing and play activities. It highlights the methodological foundations for fostering creativity in preschoolers, contemporary psychological approaches, and the importance of the social environment. The findings provide a basis for designing effective educational technologies that account for both individual and social conditions of creative development.
Keywords: Creativity psychological characteristics preschool age thinking play activity motivation social environment personal development.